Coping with stress and suicide orientation in adolescent students - Chacaliaza Uribe, Carlos Richard (2020)
The objective of the research was to determine the relationship between coping with stress and suicidal orientation in students of the Our Lady of Las Mercedes de Ica Educational Institution. The sample was of the census type, made up of 180 female students, whose ages range between 15 and 17 years, from the 4th and 5th year of secondary level. The instruments used were: Stress Coping Modes Questionnaire and Suicide Guidance Inventory. The following results were obtained: There is a very significant and negative relationship between coping with stress and suicidal orientation (r: -0.292). Therefore, it is concluded that at a greater capacity to cope with stress, the levels of suicidal orientation decrease.